Effects of motivation and depletion on the ability to resist the temptation to avoid physical activity - Rouse, P.; Ntoumanis, Nikos; Duda, J. (Taylor & Francis Inc., 2013)
Understanding the psychological processes that underpin the limited self-control resource could have important consequences for health behavior change interventions. The present study employs a 2 × 2 (autonomous/controlling × depleted/not depleted) experimental design to investigate whether an initial act of self-control influences participants' ability to employ counteractive control strategies that help to resist temptation and stick to a focal physical activity (PA) goal. Experimental instructions manipulated the environments to generate autonomy-supportive and controlling conditions. After completing either a depleting or a not-depleting Stroop task, undergraduate students' (N = 77) counteractive evaluations toward a temptation (to complete a sedentary trial with no information) and a focal goal (to complete a physically active trial that provided valuable information) were measured. Despite the successful manipulation of the experimental conditions, results indicated no significant effect of the motivational support condition or depletion condition on the value that the participants placed on a temptation or a focal goal. A significant interaction between depletion condition, autonomous motivation and controlled motivation was observed for subjective vitality. Participants high in autonomous motivations and low in controlling motivations maintained levels of subjective vitality whether depleted or not. We discuss the importance of future experimental work into the effects of temptations on self-control resources in the PA domain.